2018
DOI: 10.1021/acscentsci.8b00204
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-Controlled Stereodivergent Synthesis of Atropisomeric Multiaxis Systems

Abstract: Molecular scaffolds with multiple rotationally restricted bonds allow a precise spatial positioning of functional groups. However, their synthesis requires methods addressing the configuration of each stereogenic axis. We report here a catalyst-stereocontrolled synthesis of atropisomeric multiaxis systems enabling divergence from the prevailing stereochemical reaction path. By using ion-pairing catalysts in arene-forming aldol condensations, a strong substrate-induced stereopreference can be overcome to provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…23,24 Our work has focused on the o-phenylenes, simple polyphenylenes 25 that adopt helical conformations in solution driven by (offset) arene-arene stacking interactions parallel to the helical axis. [26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 Our work has focused on the o-phenylenes, simple polyphenylenes 25 that adopt helical conformations in solution driven by (offset) arene-arene stacking interactions parallel to the helical axis. [26][27][28][29][30][31][32][33][34] In previous work on o-phenylene-based macrocycles, we showed that amino-functionalized o-phenylene tetramers could be co-assembled with a series of rodshaped dialdehyde linkers, giving, for example, the [3 + 3] macrocycles oP 4 (Phen) 3+3 and oP 4 (DPB) 3+3 shown in Chart 1 (i.e., 3 o-phenylenes + 3 linkers). 35 The resulting twisted macrocycles [36][37][38][39][40] are shape-persistent but have well-dened degrees of conformational freedom via the foldamer moieties.…”
Section: Introductionmentioning
confidence: 99%
“…Thes trategy profited from the established iterative building block addition/stereoselective aldol sequence. [29] Thec atalyst-controlled stereodivergent synthesis,i nw hich the obstacle is the catalyst-substrate mismatch, is aw ell-explored concept in the construction of molecules with multiple stereogenic centers. [30] In sharp contrast, this concept was unrecognized when the molecule contained two or more stereogenic axes until this seminal work was addressed.…”
Section: Central-to-axial Chirality Conversion (Type B C D and E Mmentioning
confidence: 99%
“…However, modulation the sense of diastereoselectivity in an asymmetric catalytic reaction is still challenging, because the diastereochemical preference is largely governed by the inherent structure and stereoelectronic nature of the substrates 32 . To address this intrinsic problem, a series of ingenious strategies have been developed for asymmetric diastereodivergent catalysis [33][34][35] , such as using distinct catalysts [36][37][38] , change of metal cations 39 , and ligands 40,41 of the catalysts, change of reaction conditions 42,43 , stereodivergent dual catalysis [44][45][46][47][48][49][50] and stepwise control [51][52][53][54] . Nevertheless, achieving asymmetric diastereodivergent catalysis through modifications of one single type of chiral catalysts remains elusive 55,56 .…”
mentioning
confidence: 99%